Experimental Insights Into Space Weathering of Phobos: Laboratory Investigation of Sputtering by Atomic and Molecular Planetary Ions. Issue 12 (4th December 2020) - Szabo, P. S.; Biber, H.; Jäggi, N.; Wappl, M.; Stadlmayr, R.; Primetzhofer, D.; Nenning, A.; Mutzke, A.; Fleig, J.; Mezger, K.; Lammer, H.; Galli, A.; et al.
Abstract: Investigating the space weathering of the Martian moon Phobos represents an important step toward understanding the development from its origin to its present‐day appearance. Depending on Phobos' orbital position, its surface is continuously sputtered by the solar wind and planetary ions that originate in the Martian atmosphere. Based on Mars Atmosphere and Volatile Evolution measurements, it has been proposed that sputtering by planetary O + and O2 + ions dominates in the Martian tail region, where the planet mostly shadows Phobos from the solar wind. In these models, uncertainties for sputtering yield inputs still exist due to the lack of sufficient analog experiments. Therefore, sputtering measurements with O +, O2 +, C +, and CO2 + ions between 1 and 5 keV were performed using augite samples as Phobos analogs. The experimental results for O + irradiations show smaller mass changes than predicted by SDTrimSP simulations, which probably can be attributed to O implantation enabled by the Fe content of the target. Sputtering with O2 + and CO2 + in the low keV range shows no deviations in the sputtering yields attributable to molecular effects. Therefore, CO2 + ions will most likely be negligible for the sputtering of Phobos according to the current understanding of ion fluxes on the Martian moon. Ultimately, our experiments suggest that the sputtering contribution on Phobos by O ions is about 50% smaller than previously assumed. This does not change the qualitative outcome from previous modeling stating that planetary O ions are by far the dominant sputtering contribution on Phobos in the Martian tail region. Plain Language Summary: The surface of the Martian moon Phobos is continuously eroded by positively charged ions in a process called sputtering, which has changed the moon's surface over the past billions of years. Previous calculations suggest that this sputtering is caused by ions from the solar wind as well as oxygen ions that reach Phobos from the atmosphere of Mars. However, there exists a significant lack of data on how much sputtering each ion causes. This study presents laboratory experiments where the erosion of Phobos analog samples is investigated under irradiation with O +, O2 +, C +, and CO2 + ions. The focus was put on oxygen ions and molecular ions that can be expected to escape the Martian atmosphere and cause sputtering of the surface of Phobos. In general, erosion rates are found to be smaller than previously calculated. Additionally, no significant differences in sputtering effects are observed for atomic versus molecular ions. The presented experimental studies support previous conclusions about the unique sputtering conditions on Phobos: in the Martian tail regions, where the planet shadows the solar wind, oxygen ions from the atmosphere of Mars dominate the erosion of the surface of Phobos. Key Points: Experiments with Phobos analogs were carried out to evaluate the sputtering by O +, C +, O2 +, and CO2 + ions from the Martian atmosphere The sputter yield from O ions is lower than previously assumed, and no yield increases due to molecular effects were observed Previous predictions that planetary O ions will dominate sputtering in the Martian tail region are supported by the measurements presented